Is there a mismatch between employers' and university teachers' perceptions on graduate employability in Croatia? - Sedlan König, Ljerka (Array, 2019)
Employability in graduates is considered to be an outcome universities should seek to achieve. At the same time, scholars rarely differentiate between “graduateness as a state after the completion of a course, and employability as an assessment of the economic worth of a student at that time” (Glover, Law and Youngman, 2002:293). This paper aims to study employability in higher education from the employers’ and university teachers’ perspective. It highlights the most highly valued employability competencies and attributes, and paints an interesting picture of perceptions university teachers and employers have of employability characteristics. The empirical research incorporates 134 responses from employers from Croatian companies of all sizes, and 124 from University teachers from two Croatian universities: University of Rijeka and Josip Juraj Strossmayer University of Osijek. The results indicate that the university teachers and employers have similar views regarding employability characteristics, but view differently the knowledge, skills and attributes significant for employment and the contribution of higher education to the improvement of these attributes. The results point to the necessity of Croatian universities to cooperate and communicate more efficiently with employers and employer associations in developing courses, and delivering relevant subject content.